STEAM in Primary Education. Impact on Linguistic and Mathematical Competences in a Disadvantaged Context - Duo-Terron, Pablo; Hinojo-Lucena, Francisco-Javier; Moreno-Guerrero, Antonio-José; López-Núñez, Juan-Antonio (Frontiers in Education, 2022)
This research has studied the impact of the use of STEAM (Science, Technology, Engineering, Art, and Mathematics) in education, specifically in the development of linguistic and mathematical skills. The instruments used to extract the learning results were the external evaluation tests carried out by the National Institute of Educational Evaluation INEE over a period of 4 years. The study included 242 third-level primary school students from an educational center in the city of Ceuta (Spain) located in a disadvantaged area. The objectives of the study were to describe the learning results obtained in the respective competencies according to the sex and the migratory history of the students’ parents, to compare the results obtained before and during the use of STEAM and to determine if there is a correlation between the understanding of writing and problem solving. The research method was quantitative descriptive, cross-sectional and correlational. The results of the study showed that the transversal and coordinated use of STEAM improves the learning outcomes of linguistic and mathematical competence of students of the third year of Primary Education, especially speaking, oral comprehension and calculation. The results were, in general, more positive in the case of girls and students whose parents were born in Spain. The study also revealed that there is a positive correlation between reading comprehension and problem solving.